Family history of ADHD associates with stronger problem‐solving skills amongst 2‐ to 3‐year‐olds - Hendry, A.; Jones, Ejh; Andersson‐konke, L.; Agyapong, M.; Bazelmans, T.; Begum‐ali, J.; Ersoy, M.; Goodwin, A.; Pasco, G.; Falck‐ytter, T.; Johnson, Mh; Charman, T.; et al. (Wiley, 2025)
AbstractBackgroundAttention‐Deficit/Hyperactivity Disorder (ADHD) is linked to strengths in creative problem‐solving amongst school‐aged children and adults. In contrast, autism (which frequently co‐occurs with ADHD) is associated with lower generativity, and perseverative responses during problem‐solving. Little is known about how ADHD and autism traits—or broader heritable autism and ADHD phenotypes—associate with problem‐solving skills in early childhood.Methods129 UK 2‐ and 3‐year‐olds (exploratory dataset) and 74 Swedish 3‐year‐olds (confirmatory dataset) with and without a family history (FH) of ADHD and autism, completed a problem‐solving task. Parents reported on their 3‐year‐olds’ ADHD and autism traits using the Child Behaviour Checklist and Social Responsiveness Scale‐2. FH group differences in problem‐solving performance were tested using ANOVA (exploratory dataset, FH‐autism and FH‐ADHD as fixed factors) and t‐test (confirmatory and combined datasets split by FH‐ADHD). Linear regressions of problem‐solving success on autism/ADHD traits were run in both samples.ResultsCompared with peers with no FH‐ADHD, children with FH‐ADHD showed higher problem‐solving success at 2 (partial ω2 = 0.106) and 3 years (partial ω2 = 0.045) in the exploratory dataset. In the confirmatory dataset, a FH‐ADHD‐and‐autism group trended towards higher success scores compared with a no‐FH‐ADHD group (comprising FH‐autism‐only and no‐FH ADHD‐or‐autism sub‐groups) but scores were only significantly higher for children with FH‐ADHD‐and‐autism when compared with children with no FH‐ADHD‐or‐autism (gs = 0.977). ADHD (but not autism) traits were positively associated with problem‐solving performance in the exploratory (β = 0.212, p = 0.031) and combined samples (β = 0.173, p = 0.024). Effects were a consistent direction and magnitude, but not significant, in the confirmatory sample alone (β = 0.201, p = 0.103).ConclusionsConsidering a child's family history alongside their neurodivergent traits may help to identify their likely strengths, and how to access them: Children with ADHD traits and/or a family history of ADHD are likely to have an aptitude for generative problem‐solving when presented with highly motivating, ecologically valid challenges.
Keywords: Psychiatry; Pediatric; Intellectual and Developmental Disabilities (IDD); Autism; Applied and Developmental Psychology; Pediatrik; autism; executive functions; Pediatrics; Attention Deficit Hyperactivity Disorder (ADHD); Mental Illness; Psykiatri; Brain Disorders; endophenotype; Mental Health; generativity; Clinical Research; Psychology; problem-solving; Behavioral and Social Science; ADHD; Mental health